Bangalore (India) Customer’s Response to Atmospheric Elements (Colour, Lights, Music, and Aroma) in A Cafeteria. - Bhatnagar, Shrey (2013)
The study aims to enhance understanding of the effect of atmospheric elements present in the cafeteria. According to literature, the study has adopted four atmospheric elements (colour, lighting, music, and aroma) commonly found in a cafeteria that are most effective in making customers feel comfortable and attracted. This study utilises semi-structured interviews to explore the effect of atmospheric elements on fifteen participants from Bangalore having the ownership of minimum one coffee club card and are between the age of 24 and 26 years. Amongst the four atmospheric elements taken in this study, it was found music was the most important and effective atmospheric element, that was able to make customer feel complete satisfaction from the ambience followed by colour and lighting taken together, and aroma. Aroma was found to be the least attractive element in the ambience that was capable of making customers to stay for longer duration. However, it was considered to be the most important element if found missing from the ambience. The researcher suggests ways in which cafeterias and service industries can use these atmospheric elements in increasing customer attraction, comfort, and time perception. Researcher also suggests the conceptual areas for further research.